Towards an integrated assessment model for complex learning resources: Findings from an expert validation - Wesiak, G.; Al-Smadi, M.; Guetl, Christian (IEEE, 2012)
Today's e-Iearning systems meet the challenge to provide interactive, personalized environments that support self regulated learning as well as social collaboration and simulation. At the same time assessment procedures have to be adapted to the new learning environments by moving from isolated summative assessments to integrated assessment forms. In this paper an integrated model for assessment (lMA) is outlined, which incorporates complex learning resources and assessment forms as main components for the development of an enriched learning experience. For a validation the IMA was presented to a round of experts from the fields of cognitive science, pedagogy, and e-learning. The findings from the validation lead to several refinements of the model, which mainly concern the component forms of assessment and the integration of social aspects. Both aspects are accounted for in the revised model, the former by providing a detailed sub-model for assessment forms.